Contextual Knowledge as a Sociocultural Filter in TPACK: Evidence from Pre-service Javanese Language Teachers - Nur Hanifah Insani; Lynde Tan (Jurnal Pendidikan Progresif, 2026)
This research examines pre-service language teachers' perceptions of technology integration through the Extended Javanese Pre-Service Teacher (X-JPST) model, which focuses on the conceptual role of Contextual Knowledge (XK) as an integral domain extension of the TPACK framework. The participants of this research were 510 pre-service Javanese language teachers from seven universities in Indonesia who had recently completed their field teaching practice course. The research employed a validated structural Likert-scale questionnaire to examine structural relationships using Partial Least Squares Structural Equation Modelling (PLS-SEM). The results show that the Technological Knowledge (TK) variable has the most significant direct influence on TPACK, followed by Technological Pedagogical Knowledge (TPK). While the direct statistical influence of XK is modest, it functions as a mediator that facilitates the application of TK. This study suggests that pre-service teachers' awareness of Javanese sociocultural factors does not directly translate into competence in technology integration. Instead, contextual knowledge operates as a foundational sociocultural filter that shapes how they perceive themselves when using technology to teach Javanese. This key finding underscores that contextual responsiveness in technology integration must be developed through the integration of multiple knowledge domains for it to contribute to their overall TPACK. Keywords: contextual knowledge, Javanese language education, pre-service teachers, technology integration, TPACK.